The potential of futures literacy for impact-oriented business schools. (February 2023) - Spanjol, Jelena; Rosa, Aaron; Schirrmeister, Elna; Dahl, Philipp; Domnik, Dominik; Lindner, Max; de la Cruz, Marcelo; Kuhlmann, Jan-Frederic
Abstract: Current marketplace narratives increasingly demand a move from shareholder towards stakeholder primacy and responsible capitalism yielding social value creation . In parallel, the demand for entrepreneurial value creation at higher education institutions (including, but not limited to business schools) continues to grow. The intersection of these two demands, however, engenders critical tensions. While social value creation emphasizes stakeholder returns and a long-term perspective, entrepreneurial value creation revolves around investment returns and short-term agility. As a result, business schools have been grappling to find ways to incorporate a broader, holistic view on value creation into their activities. We bring together future studies and management scholars and scholarship to explore futures literacy as a potentially instrumental capability for business schools. Our investigation suggests that an interdisciplinary approach is particularly promising since both management and futures studies investigate how to engage with uncertainty and chart more desirable futures. We illustrate the instrumental role of futures literacy and foresight with an educational program built at the intersection of entrepreneurial and social value creation and with anticipatory practices at its core. We suggest that anticipatory practices are currently underutilized in business schools' curricula, outreach activities, and strategy making, and may be necessary to shape productive and constructive business schools of the future. Highlights: Business schools face growing demands to demonstrate and enable both social and entrepreneurial value creation. The intersection of these two demands engenders critical tensions in temporal and strategic frames. Futures literacy is discussed as a potential instrumental capability for business schools. Anticipatory programs and practices engendering futures literacy are generally underutilized in business schools. The potential of futures literacy in business schools is illustrated through the Startup Impact Readiness Program .